THE ROLE OF PLASMODIUM FALCIPARUM MALARIA IN ENDEMIC BURKITT'S LYMPHOMA PATHOGENESIS. - Basu Kong, Raka-Larissa. (2017)
Abstract: Endemic Burkitt's lymphoma (eBL) is the most common pediatric cancer in sub-Saharan Africa. BL is a B cell germinal center (GC)-derived lymphoma that is characterized by a reciprocal chromosomal translocation involving the c-myc gene and an immunoglobulin (Ig) locus, resulting in the constitutive activation of the c-myc proto-oncogene. This translocation occurs via the action of the enzyme activation-induced cytidine deaminase (AID). The etiology of eBL has been linked to Plasmodium (P.) falciparum malaria and Epstein-Barr virus (EBV) co-infection. While there has been much progress in explaining the mechanisms linking EBV to lymphoma development, the role of P.falciparum malaria in the genesis of eBL is only beginning to be understood. It is known that malaria caused by P.falciparum infections has profound effects on the B cell compartment and is immunosuppressive, resulting in an increased viral burden of Epstein-Barr virus (EBV). This results in higher numbers of B cells latently infected with EBV that transit the germinal center. Recently, our laboratory demonstrated that P.falciparum is capable of deregulating AID expression in B cells, and this at least in part is triggered by the malarial byproduct hemozoin. Our hypothesis is that P.falciparum heightens AID activity in the GC. This increases the risk of a c-myc translocation occurring in a GC cell latently infected with EBV, which prevents the cell from undergoing apoptosis, and thereby able to tolerate this translocation. This thesis examines the impact of P.falciparum malaria on AID expression and activity in human B cell sub-populations. Levels of AID-induced somatic mutation were compared in c-myc of ex vivo human tonsil B cell subsets from a region of holoendemic malaria compared to control cells. No significant parallel was found between higher AID expression and mutation frequencies in tonsil B cell subsets from the malaria-endemic compared to non-malaria regions. In vitro studies however yielded novel findings. P.falciparum is capable of upregulating AID expression and class switch recombination activity in tonsil B cells, as determined by the measurement of IgG1 switch circle transcript levels. In addition, the P.falciparum-specific antigen, PfEMP1 was found to be required for optimal AID induction and the data also suggest its action is via the B cell receptor (BCR). Specific B-cell subsets were probed and the impact of P.falciparum on AID activity was found to be specific to the GC and memory B cell compartments. Altogether, these studies shed more light on the induction of AID by P.falciparum and its contribution to eBL pathogenesis. This work for the first time correlates augmented AID expression induced specifically by P.falciparum with increased enzymatic activity in the site of the eBL lesion and therefore an increased risk for c-myc/Ig translocations.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Genetics.; Advisor: David Thorley-Lawson.; Committee: Erik Selsing, Philip Hinds, and John Coffin.; Keywords: Genetics, and Immunology.